2013
DOI: 10.3390/s130303615
|View full text |Cite
|
Sign up to set email alerts
|

A Humidity Sensing Organic-Inorganic Composite for Environmental Monitoring

Abstract: In this paper, we present the effect of varying humidity levels on the electrical parameters and the multi frequency response of the electrical parameters of an organic-inorganic composite (PEPC+NiPc+Cu2O)-based humidity sensor. Silver thin films (thickness ∼200 nm) were primarily deposited on plasma cleaned glass substrates by the physical vapor deposition (PVD) technique. A pair of rectangular silver electrodes was formed by patterning silver film through standard optical lithography technique. An active lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 19 publications
(20 reference statements)
0
32
0
Order By: Relevance
“…The C -value increased from 3.2183 × 10 −11 F to 9.9741 × 10 −10 F with a “ S ” of ~3000% at the signal frequency of 10 2 Hz but when the test frequency is 10 5 Hz, the capacitance varied from 1.2832 × 10 −11 to 2.8174 × 10 −11 F with “ S ” of ~120% across the RH range of 33%–95%, respectively. The sensitivity of our developed sensor is higher than that of some other ceramic based humidity sensors reported elsewhere (for example, ~2900% for porous ZnAl 2 O 4 spinel nanorod, 85% for silica nanoparticles aerogel thin films, ~966% for SiC nanowires, ~800% for thermally carbonized porous silicon, ~500% for alumina nanowire, 1490% for (PEPC + NiPc + Cu 2 O) and so on based humidity sensors) [16,56,57,58,59,60]. Therefore, in our further study the 10 2 Hz would be considered as best test frequency for the analysis of sensor characteristics.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The C -value increased from 3.2183 × 10 −11 F to 9.9741 × 10 −10 F with a “ S ” of ~3000% at the signal frequency of 10 2 Hz but when the test frequency is 10 5 Hz, the capacitance varied from 1.2832 × 10 −11 to 2.8174 × 10 −11 F with “ S ” of ~120% across the RH range of 33%–95%, respectively. The sensitivity of our developed sensor is higher than that of some other ceramic based humidity sensors reported elsewhere (for example, ~2900% for porous ZnAl 2 O 4 spinel nanorod, 85% for silica nanoparticles aerogel thin films, ~966% for SiC nanowires, ~800% for thermally carbonized porous silicon, ~500% for alumina nanowire, 1490% for (PEPC + NiPc + Cu 2 O) and so on based humidity sensors) [16,56,57,58,59,60]. Therefore, in our further study the 10 2 Hz would be considered as best test frequency for the analysis of sensor characteristics.…”
Section: Resultsmentioning
confidence: 74%
“…This result indicates that the hysteresis of our developed CMFTO electro-ceramic based humidity sensor is relatively lower than that of other different capacitive humidity sensors (i.e., ~4.16% for ZnO/Si-based, ~4.5% for SiC nanowire-based, ~4% for alumina nanowire-based, ~5% for graphene oxide-based, ~12% for (PEPC + NiPc + Cu 2 O)-based and so on) developed by other studies reported elsewhere [16,54,59,60,66]. The lower hysteresis value was obtained owing to the relatively faster adsorption and desorption rate of water molecules on the surface of the CMFTO electro-ceramic in comparison to the other materials [54,55].…”
Section: Resultsmentioning
confidence: 76%
“…Several capacitive RH sensors have been designed and produced on interdigitated gold, platinum or silver electrodes with this platform incorporating organic polymer thin films or porous ceramics such as alumina, perovskites, and porous silicon based on printing deposition or coating techniques onto a ceramic substrate [321,322]. …”
Section: Capacitive Type Humidity Sensorsmentioning
confidence: 99%
“…Moreover, the properties of these materials alter drastically due to the interaction of molecules with environmental parameters such as temperature, humidity, pressure and gases. Keeping in mind the response of organic semiconductors, several humidity [3][4][5] and multifunctional [6,7] thin film sensors have been investigated.…”
Section: Introductionmentioning
confidence: 99%